Drought stress tolerance strategies revealed by RNA-Seq in two sorghum genotypes with contrasting WUE - Fracasso, Alessandra (BMC Plant Biol, 2016)
BACKGROUND: Drought stress is the major environmental stress that affects plant growth and productivity. It triggers a wide range of responses detectable at molecular, biochemical and physiological levels. At the molecular level the response to drought stress results in the differential expression of several metabolic pathways. For this reason, exploring the subtle differences in gene expression of drought sensitive and drought tolerant genotypes enables the identification of drought-related genes that could be used for selection of drought tolerance traits. Genome-wide RNA-Seq technology was used to compare the drought response of two sorghum genotypes characterized by contrasting water use efficiency. RESULTS: The physiological measurements carried out confirmed the drought sensitivity of IS20351 and the drought tolerance of IS22330 genotypes, as previously studied. The expression of drought-related genes was more abundant in the drought sensitive genotype IS20351 compared to the tolerant genotype IS22330. Under drought stress Gene Ontology enrichment highlighted a massive increase in transcript abundance in the sensitive genotype IS20351 in “response to stress” and “abiotic stimulus”, as well as for “oxidation-reduction reaction”. “Antioxidant” and “secondary metabolism”, “photosynthesis and carbon fixation process”, “lipids” and “carbon metabolism” were the pathways most affected by drought in the sensitive genotype IS20351. In addition, genotype IS20351 showed a lower constitutive expression level of “secondary metabolic process” (GO:0019748) and “glutathione transferase activity” (GO:000004364) under well-watered conditions. CONCLUSIONS: RNA-Seq analysis proved to be a very useful tool to explore differences between sensitive and tolerant sorghum genotypes. Transcriptomics analysis results supported all the physiological measurements and were essential to clarify the tolerance of the two genotypes studied. The connection between differential gene expression and physiological response to drought unequivocally revealed the drought tolerance of genotype IS22330 and the strategy adopted to cope with drought stress. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12870-016-0800-x) contains supplementary material, which is available to authorized users.